Antonyms in the Animation of “KKN di Desa Penari” From Rizky Riplay’s Youtube Account - Riajeng Woro Megaswari; Sumarlam Sumarlam (Jurnal Lingua Idea, 2020)
This study aims to describe the cohesiveness of the discourse in terms of the lexical cohesion aspects of the use of antonymy in an animated story about "KKN di Desa Penari" from the Rizky Riplay Youtube channel. The object of this research is the antonymy found in the animated story about "KKN di Desa Penari" on Rizky Riplay's Youtube channel. The method used in the provision of data is the observing method by watching the animated story with an advanced technique using the "Simak Libat Bebas Cakap" technique (Uninvolved Conversation Observation Technique), and a second advanced technique using the note-taking technique by sorting the required lingual units as data. The method used in analyzing the data is the distributional method. The distribution method is a data analysis method in which the determinant tool is part of the language concerned. The methods used to present the results of data analysis in this study were the formal and informal methods. The results of the analysis of data, in general, showed that the antonymies that appear in the animation from the Rizky Riplay Youtube channel are in the form of polar opposition, plural opposition, relationship opposition, hierarchical opposition, and absolute opposition. This research only focuses on the lexical cohesion aspect of the antonymy usage in the animated story to find out the opposing forms of meaning that are either very opposite or just contrasting meanings.